Disaster Preparedness of Multi-Religious Houses of Worship: A Quantitative Reality Check in Harjamukti, Cirebon - Taqiuddin, Zaki Muhammad; Mariany, Aria; Rafdi, Mohd. Abi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This research stems from a growing concern regarding the vulnerability of Cirebon City, particularly the Harjamukti District, toward disasters that often bypass grassroots preparedness. My primary focus was to question the actual readiness of houses of worship as vital communal hubs. Using a quantitative descriptive approach via the Slovin formula, I gathered data from 47 multi-religious sites. The findings reveal a compelling dilemma: while risk knowledge and human resource capacity appear adequate, emergency planning and early warning systems remain alarmingly neglected. This suggests a significant gap between theoretical understanding and technical execution on the ground. Consequently, strengthening the institutional framework of these religious centers must become a policy priority for the BPBD. Future studies should further scrutinize the effectiveness of regular disaster simulations within these sacred spaces.